Pengaruh Keamanan dan Kepercayaan terhadap Keputusan Pembelian pada E-Commerce Lazada di Surabaya - Mulya Hasudungan Napitupulu; Supriyono Supriyono (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2023)
The impact of the Covid-19 pandemic is very much felt among sellers and not a few of them have gone out of business. However, with increasingly sophisticated technology, many sellers use it to sell their products online. The online sales platform that is currently widely used by the public is one of them through Lazada e-commerce. There are many risks that may occur when we shop online, for example, the goods sent do not match the picture. Therefore, this study wanted to find out what factors influence someone to make a decision to make a purchase, including consumer trust and security in the e-commerce. This research is a quantitative research with the help of SmartPLS 3.0. Distribution of data using google forms with a sample of 80 people. (From the results of the study, it was found that security had no significant effect on purchasing decisions, while trust had a significant effect on purchasing decisions. Keywords: Security;-Trust;-Buying Decision.